Secondary streamers in the primary streamer channel - Bolotov, O.; Kadolin, B.; Mankovskyi, S.; Ostroushko, V.; Pashchenko, I.; Pugach, S.; Taran, G.; Zavada, L. (Вопросы атомной науки и техники, 2019)
The propagation of the process with ionization and attachment in the remainder of the streamer channel is studied. From the simplified model consideration it is shown that in the conditions of the attachment instability development the spatially inhomogeneous perturbations move to anode. The conditions, in which the perturbations move to cathode, as it is usually observed for the secondary streamers, are discussed. Вивчається поширення процесу з іонізацією та налипанням у залишку каналу стримера. З розгляду спрощеної моделі видно, що в умовах розвитку налипальної нестійкості просторово неоднорідні збурення рухаються до анода. Обговорюються умови, за яких ті збурення рухаються до катода, як це зазвичай спостерігається для вторинних стримерів. Изучается распространение процесса с ионизацией и прилипанием в остатке канала стримера. Из рассмотрения упрощенной модели видно, что в условиях развития прилипательной неустойчивости пространственно неоднородные возмущения движутся к аноду. Обсуждаются условия, при которых эти возмущения движутся к катоду, как это обычно наблюдается для вторичных стримеров.